Formal Modeling of Communication Platforms using Reconfigurable Algebraic High-Level Nets - Modica, Tony; Hoffmann, Kathrin (Electronic Communications of the EASST, 2010)
Communication nowadays is based on communication platforms like Skype, Facebook, or SecondLife. The formal modeling and analysis of communication platforms poses considerable challenges, namely highly dynamic structures and complex behavior. Since most of the well-known formal modeling approaches are adequate only for specific aspects of communication platforms, in this paper we introduce the approach of reconfigurable algebraic high-level nets with individual tokens and show in our case study Skype that this approach is adequate for modeling the main aspects and features of communication platforms.